2014
DOI: 10.1016/j.berh.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Overview of neurodevelopment and pain research, possible treatment targets

Abstract: Pain is a common presenting and often persistent symptom for children with rheumatological disease. Pain is not clearly related to disease severity in children with inflammatory juvenile idiopathic arthritis, and presentations of non-inflammatory musculoskeletal pain are common but there is limited evidence to guide management. Pain assessment must extend beyond measures of pain severity to more fully evaluate characteristics of pain, functional impact and psychosocial effects and family interactions. Evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 130 publications
0
12
0
Order By: Relevance
“…Urge-to-cough precedes the motor response and thus may allow higher brain centers to activate those efferent inhibitory pathways in situations ranging from basic survival to social embarrassment (Gracely et al, 2007 ). Recent advances in pain research have pointed slow maturation of endogenous inhibitory descending pathways (Fitzgerald and Walker, 2009 ; Hathway et al, 2012 ) that may therefore be less efficient throughout childhood compared to adulthood (La Hausse de Lalouvière et al, 2014 ; Walker, 2014 ). As pain and cough share many similarities, it can be speculated that increased central processing of the nociceptive information caused by reduced descending inhibition may result in higher cough outcomes related to environmental pollution during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Urge-to-cough precedes the motor response and thus may allow higher brain centers to activate those efferent inhibitory pathways in situations ranging from basic survival to social embarrassment (Gracely et al, 2007 ). Recent advances in pain research have pointed slow maturation of endogenous inhibitory descending pathways (Fitzgerald and Walker, 2009 ; Hathway et al, 2012 ) that may therefore be less efficient throughout childhood compared to adulthood (La Hausse de Lalouvière et al, 2014 ; Walker, 2014 ). As pain and cough share many similarities, it can be speculated that increased central processing of the nociceptive information caused by reduced descending inhibition may result in higher cough outcomes related to environmental pollution during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive untreated pain and distress can impair the developing brain and have both short-and longterm negative consequences [62,63]. For example, neonatal inflammatory pain decreases locomotor activity in adult rats [64] and decreases pain sensitivity later in life, though more so in females than in males [65].…”
Section: (B) Postnatal Exposure To Opiatesmentioning
confidence: 99%
“…Numerous studies have already shown alterations in cough reflex characteristics throughout childhood and adolescence (Chang, 2005; Varechova et al, 2008; Ioan et al, 2014) owing to developmental changes in respiratory anatomy and physiology (Becklake and Kauffmann, 1999; Tulic et al, 2004), and evolving central processing of the nociceptive information (Walker, 2014). Recent advances in pain research have pointed toward the slow maturation of descending pathways inducing analgesia (Fitzgerald and Walker, 2009; Hathway et al, 2012) that may therefore be less efficient throughout childhood and early adolescence compared to adulthood (La Hausse de Lalouviere et al, 2014; Walker, 2014). The central processing of the afferent volley triggered by airway irritation may undergo similar developmental patterns of change resulting in less efficient suppression of cough in some children compared to adults.…”
Section: Discussionmentioning
confidence: 99%